Analisis Cluster K-Means pada Indikator Indeks Pembangunan Teknologi, Informasi, dan Komunikasi - Alfy, Zuhana Realita; Baihaqie, Ardhi Dinullah; A’ini, Zakiah Fithah (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2023)
The information and Communication Technology Development Index (IP-ICT) is used to describe the level of ICT Development, the imbalance and development opportunities of a region from the use of ICT.  IP-TIK is composed of 11 indicators, with the calculation conducted by BPS. The analysis is a K-Means Cluster analysis used to group provinces in Indonesia based on the similarity of IP-ICT constituent indicators. Grouping provinces based on IP-TIK indicators will help the government set realistic targets, track and evaluate progress over time to promote development and growth based on the capabilities of each province, so that the government is able to determine the right policies to assist in ICT development in each cluster. The results of this study obtained 4 clusters with different characteristics each. Cluster 1 and Cluster 2 require improvement in IP-TIK development.